Resilience Equilibrium Measurement and Simulation Evaluation Method of UAV Swarm Based on Agent - Zhou Guoqiang, Mu Lin, Wu Jiaren, Pan Yi, Hai Xingshuo, Gao Jihe (Hangkong bingqi, 2022)
The task execution process of UAV swarm presents the characteristics of distributed, multi-stage and confrontation. Persistent destruction events caused by intentional attacks occur from time to time. In order to ensure task execution, each flight formation in the swarm is required to be possessed with resilience. However, the existing resilience measurement methods are difficult to effectively describe the ability of UAV swarm to resist and recover from damage under long-term mission and persistent damage characteristics. Based on this, this paper intends to give a novel measurement and simulation evaluation method. Firstly, a swarm resilience equilibrium measurement method for joint reconnaissance mission is proposed. Through the description of mission process, the measurement of formation performance and mission demand are given, and the resilience equilibrium of swarm is defined. Then, based on the modeling framework, damage behavior and reconfiguration behavior model, an agent-based UAV swarm joint reconnaissance mission model is established. Afterwards, the resilience equilibrium measure is evaluated by simulation method. Finally, taking the joint reconnaissance mission of UAV swarm as an example, the case verification is carried out. The simulation results show that the proposed measurement and simulation evaluation method can provide support for the capability design of UAV swarm under continuous destruction, and ensure the reliable and stable operation of UAV swarm in mission.